Does interpupillary distance (IPD) relate to immediate cybersickness? - Doty, Taylor A.; Kelly, Jonathan W.; Dorneich, Michael C.; Gilbert, Stephen B. (2023 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2023)
Widespread adoption of virtual reality (VR) will likely be limited by the common occurrence of cybersickness. Cybersickness sus- ceptibility varies across individuals, and previous research reported that interpupillary distance (IPD) may be a factor. However, that work emphasized cybersickness recovery rather than cybersickness immediately after exposure. The current study (N=178) examined if the mismatch between the user's IPD and the VR headset's IPD setting contributes to immediate cybersickness. Multiple linear re-gression indicated that gender and prior sickness due to screens were significant predictors of immediate cybersickness. However, no significant relationship between IPD mismatch and immediate cybersickness was observed.